2017
DOI: 10.5851/kosfa.2017.37.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Sugar Replacement with Date Syrup in Prebiotic Chocolate Milk Using Response Surface Methodology

Abstract: Chocolate milk is one of the most commonly used non-fermentative dairy products, which, due to high level of sucrose, could lead to diabetes and tooth decay among children. Therefore, it is important to replace sucrose with other types of sweeteners, especially, natural ones. In this research, response surface methodology (RSM) was used to optimize the ingredients formulation of prebiotic chocolate milk, date syrup as sweetener (4-10%w/w), inulin as prebiotic texturizer (0-0.5%w/w) and carrageenan as thickenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Proteins such as lactoferrin, proteose peptone, calmodulin, prolactin, and folate binding proteins are also found in milk and considered as minor proteins ( Jovanovic et al, 2007 ). Milk proteins have positive effects on various body structures such as immune, nervous, digestive and the cardiovascular system ( Kazemalilou and Alizadeh, 2017 ; Korhonen and Pihlanto, 2006 ). Moreover, milk proteins are considered to be core of a wide variety of biologically active peptides with superior nutritive and immunological activities ( Khan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins such as lactoferrin, proteose peptone, calmodulin, prolactin, and folate binding proteins are also found in milk and considered as minor proteins ( Jovanovic et al, 2007 ). Milk proteins have positive effects on various body structures such as immune, nervous, digestive and the cardiovascular system ( Kazemalilou and Alizadeh, 2017 ; Korhonen and Pihlanto, 2006 ). Moreover, milk proteins are considered to be core of a wide variety of biologically active peptides with superior nutritive and immunological activities ( Khan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results reported by previous studies (Cadena et al., 2013; Rodriguez Furlán and Campderrós, 2017) revealed that the amount of acidity and pH in nectar samples containing stevia did not differ significantly with control sample containing sucrose. It is also reported that the type of sugar had no effect on the pH of the samples (Kazemalilou and Alizadeh, 2017). It should be noted that the pH did not change in large scale in this study (3.6–3.75) as well.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, there is a growing awareness about the adverse effects of sugar consumption, which would result in a high glycemic index and accordingly an acute increase in plasma glucose and insulin levels after consumption (Aidoo et al., 2017; Feizollahi et al., 2018). Due to these reasons, the suitable products for these groups should be formulated with sucrose substitutes (Freitas et al., 2016; Kazemalilou and Alizadeh, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Date syrup was reported to be suitable for replacing sugar in some traditional Indian and Iranian desserts (Manickvasagan, Chandini, and Al Attabi 2018;Ardali and Akbarian 2014). Improvement of organoleptic properties and chemical composition in products such as prebiotic chocolate milk and yogurt after addition of date syrup was observed (Kazemalilou and Alizadeh 2017;El-Nagga and Abd ElTawab 2012;Sayed, Kholif, and S. 2010).…”
Section: Date Syrupmentioning
confidence: 98%